Clinical outcome of Schönlein-Henoch purpura nephritis in children - Schärer, Karl; Krmar, Rafael; Querfeld, Uwe; Ruder, H.; Waldherr, Rüdiger; Schaefer, Franz (Pediatric nephrology, 1999)
We studied the long-term outcome of 64 children with biopsy-proven Schönlein-Henoch purpura (SHP) nephritis over 1-23 years of follow-up. Overall renal survival 10 years after onset was 73%. Multivariate logistic regression analysis identified initial renal insufficiency (P=0.004), nephrotic syndrome (P=0.037), and the severity of histological alterations, as defined by the proportion of glomerular crescents (P=0.051), as significant independent predictors of progressive renal failure. Four patients followed for more than 19 years showed glomerular damage after transient recovery. Eight children with crescentic nephritis associated with a rapidly progressive course and/or persistent nephrotic syndrome were treated by at least seven sessions of plasma exchange (PE) within 16 weeks of onset of purpura. During treatment serum creatinine levels dropped in each patient from a mean of 2.3 to 1.1 mg/dl, followed by a rebound increase. Repeated courses of PE in 5 patients produced comparable responses. Four patients undergoing PE reached end-stage renal disease at 1.2.-3.7 years after onset, whilst 3 finally were in preterminal renal failure (creatinine 3.2-6.1 mg/dl after 7-13.5 years), and 1 patient reached a normal glomerular filtration rate. Our experience suggests that initial renal insufficiency is the best single predictor of the further clinical course in children with SHP nephritis. Early PE appears to delay the progression in some patients with severe, rapidly progressive forms of the disease.
Gesehen am 20.01.2021